FRI0052 Targeting Tristetraprolin To Treat Inflammatory Arthritis. (15th July 2016) - Ross, E.; Naylor, A.; Kollias, G.; Filer, A.; Dean, J.; Buckley, C.; Clark, A.
Abstract : Background: Aberrant activation of MAPK p38 signalling contributes to pathogenesis of RA 1 . MAPK p38 promotes expression of inflammatory mediators via phosphorylation of the mRNA destabilising protein Tristetraprolin (TTP) at two serine residues. These phosphorylations a) protect TTP protein from destruction by the proteasome, and b) inactivate it, resulting in stabilisation of target mRNAs such as TNF 2, 3 . Dephosphorylation and activation of TTP is mediated by the phosphatase PP2A. Disruption of the murine TTP gene ( Zfp36 ) causes a severe, pervasive inflammatory syndrome, including erosive arthritis. The phenotype is largely due to increased stability of TNF mRNA and overexpression of TNF protein 4 . TTP protein is reported to be strongly expressed in the RA synovium 5 . However, the cells expressing TTP were not identified, and the relationship with inflammation was not explored. Objectives: To test the hypothesis that synovial inflammation requires phosphorylation and inactivation of TTP, and that, conversely, synovial inflammation may be inhibited by promoting the dephosphorylation and activation of TTP. Methods: The expression of TTP and its relationship with p38 activation in normal and RA synovial tissue were examined by confocal microscopy. A knock-in mouse strain ( Zfp36aa/aa ) was generated, in which sites of p38-dependent phosphorylation were subsituted by non-phosphorylatable alanine residues 3 . Experimental arthritis was induced by K/BxN serum transfer. In vitro and in vivo experiments were performed to test anti-inflammatory effects of a compound that activates the phosphatase PP2A. Results: TTP expression was significantly higher in RA than non-inflamed synovium, detected in macrophages, vascular endothelial cells and some synovial fibroblasts, and co-localised with MAPK p38 activation. The Zfp36aa/aa mouse, in which TTP is non-phosphorylatable and constitutively active, were resistant to induction of experimental arthritis. Protection against arthritis was dependent on constitutive TTP function in both haematopoietic and non-haematopoietic compartments. In vitro, a PP2A activating compound impaired the expression of TNF in a manner dependent on the modulation of TTP function. In vivo, it reduced inflammation and prevented bone erosion in the K/BxN serum transfer model of RA. Conclusions: The phosphorylation state of TTP is a critical determinant of inflammatory responses, and a tractable target for novel anti-inflammmatory treatments. References: Clark, A.R. & Dean, J.L. The p38 MAPK Pathway in Rheumatoid Arthritis: A Sideways Look. Open Rheumatol J 6, 209–219 (2012). Sandler, H. & Stoecklin, G. Control of mRNA decay by phosphorylation of tristetraprolin. Biochem Soc Trans 36, 491–496 (2008). Ross, E.A., et al. Dominant Suppression of Inflammation via Targeted Mutation of the mRNA Destabilizing Protein Tristetraprolin. J Immunol 195, 265–276 (2015). Brooks, S.A. & Blackshear, P.J. Tristetraprolin (TTP): Interactions with mRNA and proteins, and current thoughts on mechanisms of action. Biochim Biophys Acta 1829, 666–679 (2013). Brooks, S.A., et al. Analysis of the function, expression, and subcellular distribution of human tristetraprolin. Arthritis Rheum 46, 1362–1370 (2002). Acknowledgement: This work was supported by programme grant 19614 from ARUK Disclosure of Interest: None declared